STATUS GIZI ANAK PRA SEKOLAH DENGAN INDIKATOR IMT/U DI TK/RA WILAYAH KELURAHAN KARANG PULE KECAMATAN SEKARBELA KOTA MATARAM - Endy Bebasari Ardhana Putri (STIKES Mataram, 2019)
It is known from the NTB Province Health Profile data in 2017, there were 23.5% of children under five suffering from malnutrition, namely overweight or underweight. In the city of Mataram itself, there are still 32% including malnutrition, 1% of them suffer from over nutrition and obesity. Malnutrition in children under five, where this age group also includes pre-school children can occur if the diet is not right. Lack of protein calories can result in underweight nutritional status and excess protein calories that are not matched by physical activity can cause excess weight and even obesity. The purpose of this study was to describe the characteristics of pre-school children in the city of Mataram according to their nutritional status based on gender. Nutritional status as measured by the Body Mass Index (BMI) indicator by age. Samples were taken accidentally from all kindergartens / RAs located in Karang Pule Sekarbela village with a total of 63 children. The study design used was cross sectional. The data analysis test uses the Chi square descriptive test with an error rate of 5%. From the research conducted, it was shown that the majority of pre-school children in the Sekarbela District area had normal nutritional status (51%), but there were still malnutrition including weight loss and obesity (49%). The conclusion of this study is that almost 50% of preschool children have malnutrition nutritional status and there is no difference in nutritional status between girls and boys (p = 0.307). Considering that there are still malnutrition in pre-school children who are thin or even more obese, it is necessary to intervene from the local health workers to tackle malnutrition in preschool children not only to focus on increasing the child's weight, but also to help children have normal nutritional status .